Assembly of Two‐Dimensional DNA Arrays Could Influence the Formation of Their Component Tiles. (27th July 2022) - Paluzzi, Victoria E.; Zhang, Cuizheng; Mao, Chengde
Abstract: Tile‐based DNA self‐assembly is a powerful approach for nano‐constructions. In this approach, individual DNA single strands first assemble into well‐defined structural tiles, which, then, further associate with each other into final nanostructures. It is a general assumption that the lower‐level structures (tiles) determine the higher‐level, final structures. In this study, we present concrete experimental data to show that higher‐level structures could, at least in the current example, also impact on the formation of lower‐level structures. This study prompts questions such as: how general is this phenomenon in programmed DNA self‐assembly and can we turn it into a useful tool for fine tuning DNA self‐assembly? Abstract : Data that show higher level structures, i. e. two‐dimensional arrays, could impact the formation of their component tiles, are presented. Herein, the branched Kissing Loop motif has enabled us to observe this phenomenon with regard to programmed DNA self‐assembly.